The DUF348 domains of resuscitation promoting factor 2 play important roles in the enzymatic and biological activities in Rhodococcus erythropolis KB1 - Jianhui Fu; Jixiang Chen; Yonggang Wang; Dan Luo; Tianfeng Wang; Qingfang Zhang (PeerJ)
Rhodococcus erythropolis KB1 is a member of the Actinomycetota and a petroleum-degrading bacterium, isolated from soil contaminated with petroleum products. The resuscitation-promoting factors (Rpf) widely exist among Actinomycetota, which revive the viable but nonculturable (VBNC) state cells and facilitate growth of normal cells. The Rpf2 of the R. erythropolis KB1 is the most complex Rpf protein, which consists of the conserved Rpf domain, one G5 domain and three DUF348 domains. The protein demonstrates muralytic activity and growth-promoting and resuscitation effect, but the exact roles of these DUF348 domains in the enzymic and biological activities remain unclear. In this paper, the recombinant plasmids containing rpf2 genes with different DUF348 domain deletion were constructed and expressed in Escherichia coli. The enzymatic and biological activities of the mutated Rpf2 proteins were examined. The results showed that the enzymatic activities of the mutated Rpf2 proteins with 1, 2, and 3 DUF348 deletion decreased by 26.27%, 38.17%, and 42.56% respectively when compared with that of the wild-type Rpf2. A negative correlation between the number of DUF348 deletions and the growth-promoting and resuscitation effect on R. erythropolis KB1 cells were also observed. The muralytic activities of the mutated Rpf2 proteins showed stability at the temperature range of 20 °C to 40 °C, but showed sharp declines at 50 °C, with the activity dropping by 50.07% to 90.06%, and complete loss at 70 °C and 80 °C, underscoring importance of the DUF348 in thermal stability of the Rpf2. Zn2 + and Mn2 + slightly enhanced the muralytic activity, while Mg2 +, Ca2 + and Co2 + had negligible effects. These findings offered significant insights into mechanism of the Rpf action, emphasizing the critical role of the DUF348 domain.